Association Between Blood Sugar Levels and Blood Pressure in Individuals with Diabetes Mellitus: A Cross-Sectional Study - Ardila, Lusiana; Munir, Nur Wahyuni (Omni Nursing Journal, 2025)
Background: Diabetes is a chronic metabolic disease characterized by elevated blood glucose levels, which over time can cause serious damage to the heart, blood vessels, eyes, kidneys, and nerves. Objective: This study aimed to determine the association between blood sugar levels and blood pressure in individuals with diabetes mellitus in the working area of Tomia Health Center. Methods: This research was descriptive-analytic in nature and used a cross-sectional design. The sample size was 73 respondents which was determined using Slovin formula. Bivariate analysis employed the Pearson correlation test. Results: The results showed a significant relationship between blood sugar levels and blood pressure in patients with diabetes mellitus, with a p-value of 0.000 (p < α), indicating that the hypothesis (Ha) was accepted. Conclusion: The fluctuations in blood sugar levels are significantly associated with changes in blood pressure among patients with diabetes mellitus.